Reactive natural phosphate and nitrogen fertilizers in Marandu grass fertilization - Cabral, Carlos Eduardo Avelino; Cabral, Luciano da Silva; Bonfim-Silva, Edna Maria; Carvalho, Kassio dos Santos; Abreu, Joadil Gonçalves de; Cabral, Carla Heloisa Avelino (Comunicata Scientiae, 2019)
This study aimed to identify a nitrogen fertilizer in order to allow the use of reactive natural phosphate (phosphate rock) in the fertilization of Marandu grass (palisade grass cv. Marandu) in a sandy clayey Oxisol with low phosphorus content. The experiment was performed in a plant nursery at the Federal University of Mato Grosso (UFMT), in a completely randomized experimental design, in a split-plot scheme, with eight replications. The plots consisted of six fertilization treatments of the Marandu grass (Brachiaria brizantha cv. Marandu), divided into four treatments applied after liming and two treatments without liming. Treatments in the presence of liming were: single superphosphate and urea, single superphosphate and ammonium sulfate, urea and reactive natural phosphate, reactive natural phosphate and ammonium sulfate. Treatments without liming were: reactive natural phosphate and urea, reactive natural phosphate and ammonium sulfate. For this experiment, three growth times were evaluated. Ammonium sulfate allows the use of reactive natural phosphate in the fertilization of the Marandu grass even after liming, whilst urea does not provide sufficient acidity.